2021
DOI: 10.1001/jamaoncol.2021.0379
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Randomized Clinical Trial in the Era of Precision Oncology

Abstract: The randomized clinical trial (RCT) in oncology has evolved since its widespread adoption in the 1970s. In recent years, concerns have emerged regarding the use of putative surrogate end points, such as progression-free survival (PFS), and marginal effect sizes. OBJECTIVE To describe contemporary trends in oncology RCTs and compare these findings with earlier eras of RCT design and output. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort study of systemic therapy RCTs in breast, colorectal, and non-small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 31 publications
(50 reference statements)
4
82
0
Order By: Relevance
“…It has led to the relaxation of MA rules to quickly allow entrance of new cancer therapies into the worldwide market. Two main regulatory concepts have been used to facilitate this: i. the extended use of surrogate endpoints at registration time [26], and ii. the reliance on the regulatory decisions taken by reputed regulators [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has led to the relaxation of MA rules to quickly allow entrance of new cancer therapies into the worldwide market. Two main regulatory concepts have been used to facilitate this: i. the extended use of surrogate endpoints at registration time [26], and ii. the reliance on the regulatory decisions taken by reputed regulators [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Two main regulatory concepts have been used to facilitate this: i . the extended use of surrogate endpoints at registration time [ 26 ], and ii . the reliance on the regulatory decisions taken by reputed regulators [ 27 – 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Jairam et al 34 found that among phase 3 oncology clinical trials, RCTs of targeted systemic agents were more likely to be externally funded. Del et al 11 reported that, over time, there has been an increase in the proportion of RCTs with industry funding. Our analyses found that 77 RCTs (29.4%) were externally funded.…”
Section: Discussionmentioning
confidence: 99%
“…Another important challenge for cancer research has been the definition of endpoints capturing relevant outcomes in each research setting as timely as possible, in order to provide the patient with rapid access to innovative therapeutics. Ideally, surrogate endpoints with strong correlation with clinically meaningful outcomes should serve this purpose, but few comply to this definition ( 70 , 71 , 72 ). As an example, after granted accelerated approval for several Immune Checkpoint Inhibitors, FDA announced that four indications were voluntarily withdrawn, and six others were under review since reported results from confirmatory trials have not verified clinical benefit ( 73 ).…”
Section: Introductionmentioning
confidence: 99%